RFID Indoor Localization Using Statistical Features. Issue 8 (17th November 2021) - Bergeron, Frédéric; Bouchard, Kevin; Gaboury, Sebastien; Giroux, Sylvain
Abstract: In this paper, we present a method that uses the signal strength indication of RFID antennas with statistical features to perform relative positioning in a smart home. The goal of the proposed method is to enable the tracking of most objects inside a smart home in real-time, allowing activity recognition based on this tracking. This paper also introduce a new dataset of 4 100 000 RFID data collected in a real full-scale smart home setting. The dataset is available for the community. The method has an accuracy of 95.5% which is similar to previous work but require a fifth of the time to compute.